Changes in reproductive organs, semen characteristics and intra-testicular oxidative stress in adult male rats caused by azithromycin - El-Sayed, Mossad; Kandiel, Mohamed; Ebied, Dalia (International Journal of Pharmacology and Toxicology, 2017)
This study aimed to evaluate the numerous azithromycin (as a member of macrolides) effects on the male reproductive organs, spermio-gram, testicular oxidative stress markers of adults’ male albino rats. Azithromycin was administered orally once daily to male rats (200-250 b.wt.) at a dose of 45 mg (therapeutic) or 90 mg/kg b.wt. (double-therapeutic) for three or six days and scarified at the first, thirty and sixty days after the last dose of administration. A significant decrease as the index weight of the reproductive organs as well as sperm motility, livability and cell concentration, but sperm abnormalities increased at varying times post-treatment with azithromycin administration. Testosterone hormone level did not vary significantly after azithromycin dosing for three days along the experimental period. However, it differed at the first day after the end of azithromycin dosing for six days. The intra-testicular oxidative stress alteration mostly occurred at the thirty-day post-treatment in the three- and six-days protocols. In the three-days protocol, there was a significant decrease in malondialdehyde level and superoxide dismutase enzyme activity in a double-therapeutic group. In the six-days regimen, there was an increased activity of catalase enzyme, accompanied with a significant decrease in malondialdehyde levels as well as glutathione peroxidase enzymes. Double therapeutic dose for six days’ treatment was associated with vascular congestion and perivascular inflammatory cells and ho-mogenous eosinophilic material infiltration into the stroma of testes. The lumen of seminiferous tubules and epididymis showed azoo-spermia. From these results, it could be concluded that azithromycin administration has hazard effects on male adult’s rats’ fertility governed with the spermiogram, oxidative stress and the histopathological alternations during the post-treatment period.